Predominant expression and activity of vacuolar H+-ATPases in the mixed segment of the wood-feeding termite Nasutitermes takasagoensis. (July 2015) - Kumara, Rohitha P.; Saitoh, Seikoh; Aoyama, Hiroaki; Shinzato, Naoya; Tokuda, Gaku
Graphical abstract: Highlights: Transcriptome analysis of the mixed segment was performed for the first time. Transcripts encoding V-ATPase were among the most dominantly detected genes. Quantitative PCR verified predominant expression of V-ATPase in the mixed segment. V-ATPase in the mixed segment showed higher activity than in the adjacent gut parts. Abstract: The mixed segment is a unique part of the gut present only in the most apical lineage of termites and consists of a complex of overlapping mesenteric and proctodeal epithelia. In spite of its unique structure, the physiological functions of the mixed segment have been poorly studied. We performed transcriptome analysis to identify functional enzymes acting in the mixed segment of the wood-feeding higher termite Nasutitermes takasagoensis . We sequenced the transcripts (4563 isotigs) of the mixed segment and compared them with those of the midgut (4813 isotigs) and the first proctodeal segment (3629 isotigs). We found that vacuolar H + -ATPase (V-ATPase) subunits were predominant in the mixed segment, which was confirmed by RT-qPCR analysis. The V-ATPase activity in these three tissues was in a good agreement with the expression patterns, suggesting that V-ATPase is a prevalent enzyme in the mixed segment of the termites. The results confirmed the proposed role of the mixed segment as a transporting epithelium.